الأداء التسويقي من منظور التسيير التوقعي للوظائف والكفاءات -دراسة حالة مؤسسة اتصالات الجزائر موبيليس- - قداش, سمية; تيشات, سلوى; مزهودة, نور الدين (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى التعرف على أثر التسيير التوقعي للوظائف والكفاءات على الأداء التسويقي، وذلك من خلال إجراء دراسة ميدانية على مؤسسة الهاتف النقال موبيليس، حيث شملت عينة الدراسة 31 مسؤولا من وظيفة إدارة الموارد البشرية، وظيفة التسويق، ووظيفة التسيير الاستراتيجي، اعتمدنا في دراستنا هذه على الملاحظة العلمية، والاستبيان من اجل معرفة واقع العلاقة الارتباطية بين التسيير التوقعي والأداء التسويقي. ولتحليل الاستبيان، تم الاعتماد على برنامج (Spss) ، من أهم النتائج المتوصل إليها وجود تطبيق فعلي لنموذج التسيير التوقعي للوظائف والكفاءات في المؤسسة محل الدراسة، وجود علاقة طردية قوية بين أبعاد التسيير التوقعي للوظائف والكفاءات والأداء التسويقي في مؤسسة الهاتف النقال موبيليس الجزائر. This study aims to identify the impact of the predictive management of jobs and competencies on marketing performance, by conducting a field study on the Mobilis mobile phone institution, where the study sample included 31 officials from the human resources management function, the marketing function, and the strategic management function. Depended On scientific observation and questionnaire in order to know the reality of the correlation between predictive management and marketing performance. To analyze the questionnaire, we adopted on the (Spss) program, one of the most important results obtained is the existence of an actual application of the model of predictive management of jobs and competencies in the organization under study, presence of a strong positive relationship between the dimensions of predictive management of jobs, competencies and marketing performance in the Mobile Phone Corporation Mobilis Algeria.
Marketing performance from the perspective of predictive management of jobs and competencies Case study of Algeria Telecom Mobilis
مقال
Keywords: أداء تسويقي ; تسيير توقعي للوظائف والكفاءات ; مؤسسة اتصالات الجزائر موبيليس